Evaluating dried salted cod amino acid signature for nutritional quality assessment and discriminant analysis - Quaresma, M. A. G.; Pereira, G.; Nunes, M. L.; Sponda, C.; Jardim, A.; Gonçalves, H.; Santos, C.; Roseiro, L. C. (Frontiers in Nutrition, 2023)
1 Aim: This study aims to answer 3 scientific questions: 1) Are the protein content and amino acid profile of dried salted cod influenced by cod’s species (Gadus morhua and Gadus macrocephalus)?; 2) Are the protein content and amino acid profile of dried salted cod influenced by the geographical area of capture (Iceland and Norway)? and 3) Does the amino acid profile possess discriminant potential between species and geographical harvesting areas? 2 Methods: Total protein content was determined by the Kjeldahl method, by the AOAC procedures. The amino acid profile was analyzed by HPLC with fluorescence detection (at excitation and emission wavelengths of 338 and 425 nm, respectively). Results: The Atlantic cod presented higher contents of total protein (33.90 versus 33.10 g/100 g of cod edible portion; P=0.017) and complete amino acid contents (32.52 versus 32.04 g/100 g of cod edible portion; P=0.015) but displayed the lower percentage of indispensable amino acids (32.16 versus 32.83 g/100 g of protein; P<0.001) than Pacific cod. Among the Atlantic cod harvesting locations, the Norwegian cod displayed higher total amino acid contents (96.91 versus 96.81 g/100 g of protein; P=0.012) and a higher percentage of indispensable amino acids (35.38 versus 28.94 g/100 g of protein; P=0.042) than the Icelandic counterpart. A correct classification of 100% was obtained for the Pacific and Icelandic cod varieties, but the classification accuracy in the Norwegian cod was of just 86.67%. Conclusion: The comparison of cod species showed that the Atlantic cod had a significantly lower EAAI than the Pacific cod (P<0.001; 88.23 versus 88.61). On the other hand, comparing the two origins in the Atlantic cod, showed that the Norwegian cod displayed a significantly higher EAAI than the Icelandic cod (99.15 versus 77.32). The assessment of the EAAI allows the classification of the protein’s nutritional quality, allowing us to classify both cod species as a good protein source for the human diet. However, within the Atlantic cod, the Norwegian cod is classified as high quality, while the Icelandic cod attain the classification of useful quality.